LATE DEVONIAN DIAMONDIFEROUS KIMBERLITE AND ALKALINE PICRITE (PROTO-KIMBERLITE?) MAGMATISM IN THE ARKHANGELSK REGION, NW RUSSIA - Mahotkin I.L.; Gibson S.A.; Thompson R.N.; Zhuravlev D.Z.; Zherdev P.U. (My University, 2000)
Widespread penecontemporaneous igneous activity affected NW Russia (the Kola Peninsula and adjoining areas to the SE around Arkhangelsk) during the Late Devonian (360–380 Ma). Magmatism varies from tholeiitic basalts, erupted in the axial regions of former Middle Proterozoic (Riphean) rifts, to strongly alkaline rock-types on and marginal to Archaean cratons. NNE of Arkhangelsk kimberlites, olivine lamproites and alkaline picrites were emplaced; all these rock-types are diamondiferous to varying extents. Higher TiO 2 (and also total Fe) distinguish predominantly mica-poor Eastern Group kimberlites (TiO 2 = 2·4–3·1 wt %) and spatially associated alkaline picrites (TiO 2 = 3·2–3·7 wt %) from nearby micaceous Western Group kimberlites (TiO 2 = 0·8–1·1 wt %). Each rock-type also has distinctive rare earth element (REE) patterns, and εNd ranges: micaceous kimberlites, (La/Yb) n = 19·1–44·4, εNd = −2·4 to −3·6; olivine lamproites, (La/Yb) n = 76·9, εNd = −4·6 to −4·7; mica-poor kimberlites, (La/Yb) n = 86·3–128·2, εNd = 0·0–2·5; alkaline picrites, (La/Yb) n = 13·1–17·9, εNd = 0·1–1·1. Variations in the petrography and bulk-rock chemistry of the Arkhangelsk kimberlites are superficially similar to South African Group I and II kimberlites. Despite their field proximity, the alkaline picrite REE patterns contrast with those of the kimberlites. Instead, they closely resemble those of ‘protokimberlites’, the hypothetical magmas calculated to have precipitated South African kimberlite subcalcic clinopyroxene, garnet and ilmenite megacrysts at base-of-lithosphere depths (∼200 km). Our new data, combined with published studies of Arkhangelsk kimberlites and the silicate inclusions in their diamonds, support a genetic model where protokimberlite magmas separated from sub-lithospheric convecting mantle at several hundreds of kilometres depth. During their uprise through ∼200 km thick lithosphere, some magma batches dissolved predominantly ilmenite on a minor scale and erupted as mica-poor alkaline picrites and kimberlites. Others reacted wholesale with fusible lithospheric components to produce micaceous alkaline picrites and diamondiferous kimberlites.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская